INTERNATIONOAL LEGAL ASPECTS OF SERBIAN AND YUGOSLAV DIPLOMACY AT THE END OF XIX AND THE BEGINNING OF XX CENTURY (Heritage, 2024)
Diplomacy has perpetually captivated the attention and fascination of a broad spectrum of individuals, including scholars, historians, legal experts, politicians, and others since the Old Ages. The reason for the interest and curiosity in diplomacy is that diplomacy was an activity that was performed far away from the public eye and it was, to the greatest extent, secretive and strictly confidential. This secrecy surrounding diplomacy often created various unreal and incredible mystifications and legends.The special interest in diplomacy, not only of the professional and scientific public, but also that of the general public, on an international scale, arose after the World War I, and even more so after the World War II. These were the most terrible wars to date, both in terms of the number of participating countries, including millions of victims and unprecedented war destruction and damage. In the context of the interest of the wider public in diplomacy, there is also interest in certain diplomats who participanted in numerous diplomatic activities.At the end of XIX and beginning of XX century, Serbia and later Yugoslavia faced the challenge of maneuvering through a complex geopolitical environment, highlighting the importance of diplomatic efforts in shaping its future. Serbia and later Yugoslavia never attacked neither it have evera started a war or an arm conflict, but only defended itself from the agressors who attacked it. As a small nation in the Balkans, Serbia aimed to affirm its sovereignty and bolster its position amidst the intricate network of alliances and conflicts prevalent in Europe at the time. Diplomacy played a crucial role in gaining international recognition for Serbia. At that time Serbian diplomacy, and later that of Yugoslavia, was very highly ranked and its diplomats were educated in very prestigious Universities in Europe, thus they were well trained for their jobs.
Keywords: Diplomacy, Internatonal Law, Serbia, Yugoslavia, war, writers as diplomats